Membangun Proxy Server dengan SQUID berbasis Open Source Software Fedora (Studi Kasus Squid Server Universitas Sahid Surakarta) - Permana, Tatok Andri; susilo, dahlan; Kristiawan, Ade (JURNAL GAUNG INFORMATIKA, 2009)
The development of internet technology ensures the availabilities of information anywhere and anytime. Internet users can access the required information via the internet very easy, that is no exception for students. However, if the availability of the information is not managed properly can cause some problems which can arise includeaccessing sites that are not related to education materials (such as porn sites, online gaming sites, etc.). Whereas sites like it usually requires a large bandwidth and are often infiltrated with warm or trojan. Also, often if the students want to access an internet, users must access to the sites server directly. This conditions will reduce access-speed. The university need a solution for it, so the construction of a Proxy Server can do. At Sahid University of Surakarta previously built systems using a proxy server with FreeBSD OS that has some weaknesses. Of weakness, the need to develop new systems to overcome the weaknesses encountered. The system will be constructed that is a proxy server using Fedora OS and Squid 2.6 as supporting software. Development of the new system is a proxy server, designed to block porn sites, online gaming sites, as well as speed up Internet access.The development of a proxy server system at Sahid University of Surakarta produce a faster internet access. Internet access management on the proxy server can block sites that do not relate to the world of education as well as network security firewalls and network control client. This system can also manage Internet access based on time and MAC Address of computer clients.